Biomechanics of sports-induced axial-compression injuries of the neck - Ivancic, P. C. (Journal of Athletic Training, 2012)
Abstract: Context: Head-first sports-induced impacts cause cervical fractures and dislocations and spinal cord lesions. In previous biomechanical studies, researchers have vertically dropped human cadavers, head-neck specimens, or surrogate models in inverted postures. Objective: To develop a cadaveric neck model to simulate horizontally aligned, head-first impacts with a straightened neck and to use the model to investigate biomechanical responses and failure mechanisms. Design: Descriptive laboratory study. Setting: Biomechanics research laboratory. Patients or Other Participants: Five human cadaveric cervical spine specimens. Intervention(s): The model consisted of the neck specimen mounted horizontally to a torso-equivalent mass on a sled and carrying a surrogate head. Head-first impacts were simulated at 4.1 m/s into a padded, deformable barrier. Main Outcome Measure(s): Time-history responses were determined for head and neck loads, accelerations, and motions. Average occurrence times of the compression force peaks at the impact barrier, occipital condyles, and neck were compared. Results: The first local compression force peaks at the impact barrier (3070.0 ± 168.0 N at 18.8 milliseconds), occipital condyles (2868.1 ± 732.4 N at 19.6 milliseconds), and neck (2884.6 ± 910.7 N at 25.0 milliseconds) occurred earlier than all global compression peaks, which reached 7531.6 N in the neck at 46.6 milliseconds (P < .001). Average peak head motions relative to the torso were 6.0 cm in compression, 2.4 cm in posterior shear, and 6.4° in flexion. Neck compression fractures included occipital condyle, atlas, odontoid, and subaxial comminuted burst and facet fractures. Conclusions: Neck injuries due to excessive axial compression occurred within 20 milliseconds of impact and were caused by abrupt deceleration of the head and continued forward torso momentum before simultaneous rebound of the head and torso. Improved understanding of neck injury mechanisms during sports-induced impacts will increase clinical awareness and immediate care and ultimately lead to improved protective equipment, reducing the frequency and severity of neck injuries and their associated societal costs.